THE NON-BRAID GRAPH OF DIHEDRAL GROUP Dn - Muhammad, Hubbi; Maharani, Rambu Maya Imung; Nurhayati, Sri; Wadu, Mira; Susanti, Yeni (Journal of the Indonesian Mathematical Society, 2024)
We introduce the non-braid graph of a group G, denoted by ζ(G), as a graph with vertex set G \ B(G), where B(G) is the braider of G, defined as the set {x ∈ G | (∀y ∈ G)xyx = yxy}, and two distinct vertices x and y are joined by an edge if and only if xyx ̸ = yxy. In this paper particularly we give the independent number, the vertex chromatic number, the clique number, and the minimum vertex cover of non-braid graph of dihedral group Dn